Mathematical Model for Water Transfer in Multidomain Food Packed in Permeable Packaging. (7th September 2012) - Chu, Zhenhui; Lu, Lixin; Wang, Jun
Abstract : In terms of composite food systems, the food shelf life is affected by the moisture migration between the package and the external environment as well as among the components. In this paper, the water transfer behaviour in multidomain food packed in permeable packaging was studied, and a mathematical model based on Fick's and Henry's laws was developed to predict the unidirectional moisture transferring in composite food products packed with permeable packages. By using 0.6 water activity ( a w ) dried slice of pork and 0.7 a w piece of hawthorn as middle a w analogues, the model was validated with a pair of two‐component composite food systems (biscuit with the slice of pork and biscuit with the piece of hawthorn), and the moisture content changing with time in biscuits was tested and compared with the predicted value, showing high correspondence and consistency. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : In this paper, the water transfer behaviour in multidomain food packed in permeable packaging was studied, and a mathematical model based on Fick's and Henry's laws was developed to predict the unidirectional moisture transferring in composite food products packed with permeable packages. The model was validated with a pair of two‐component composite food systems, and the moisture content changing with time was tested and compared with the predicted value, showing high correspondence and consistency.